2019
DOI: 10.23887/ekuitas.v7i2.17986
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Lingkungan Belajar dan Keinginan untuk Meningkatkan Pengetahuan Terhadap Niat Memilih Karier Akuntansi

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh persepsi lingkungan belajar (PLB) terhadap niat dalam memilih karier akuntansi (MKA), dengan variabel mediasi keinginan untuk meningkatkan pengetahuan saat ini (KMP). Pendekatan penelitian survei online diadopsi untuk menguji variabel dalam penelitian ini. Data yang digunakan adalah hasil survei pada 503 mahasiswa jurusan akuntansi di wilayah Jawa. Data tersebut kemudian dianalisis dan hipotesis diuji menggunakan partial least squares structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The learning environment can also empower knowledge and positively impact the student's career selection. A wellstructured learning environment can increase students' interest and engagement in the lesson contents and subjects, which shape their desire for future careers (Hatane & Setiawan, 2019). Jahanpour, Azodi, Azodi, and Khansir (2016) examined factors hindering the clinical learning of prospective trainee nurses and found that an unsatisfactory practical learning environment and incompetent teaching staff and instructors hindered the assimilation of theoretical and practical skills among students, which affected the outcome of their training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The learning environment can also empower knowledge and positively impact the student's career selection. A wellstructured learning environment can increase students' interest and engagement in the lesson contents and subjects, which shape their desire for future careers (Hatane & Setiawan, 2019). Jahanpour, Azodi, Azodi, and Khansir (2016) examined factors hindering the clinical learning of prospective trainee nurses and found that an unsatisfactory practical learning environment and incompetent teaching staff and instructors hindered the assimilation of theoretical and practical skills among students, which affected the outcome of their training.…”
Section: Literature Reviewmentioning
confidence: 99%